Asālīb Ta’līm Mahārati An-Nuthqi Ash-Shahih Lillugatil Arabiyyah ( Dirāsah Tahlīliyyah ‘Alā Shautiyyāt Kitāb Al-Arabiyyah Baina Yadaik) - Ruhul Kudus; Fatkhul Ulum; Mohd Shauki Bik Bin Mohd Kasim (Fakultas Tarbiyah Program Studi Pendidikan Bahasa Arab Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2023)
This research aims to determine the method of teaching the correct pronunciation skill of the Arabic language in the Arabic book in your hands. The reason for choosing this topic is to provide an overview and information about the Arabic book in your hands and some of its advantages. This research is descriptive and analytical research, and the method of data collection is the method of observation and documentation on the subject, and the method of data analysis is through the analysis of the content contained in the Arabic book in your hands. One of the advantages of this book and its analysis first: presenting phonetics before other skills. Second: Training students on minor binaries realizes that the phonetic system in Arabic is different from the phonetic system of his mother tongue, Third: Providing the student with the opportunity to repeat and imitate phonetic. Fourth: Exercises to recreate new vocabulary with sounds, Fifth: Exercises on reciting a set of Quranic verses The aim of this training is to be fluent in the pronunciation of Arabic sounds. Sixth: Vocal exercises ended up producing and trying to present sounds that he thinks are difficult for the student of the Arabic language